NHC Communications Inc. announces financing of up to US$2.5 million (Canada NewsWire, 2005)
The issuance of the Debentures and the Warrants is subject to regulatory approval and closing will be subject to the satisfaction of certain conditions in favour of the investor. The private placement will be subject to certain terms and conditions, including those set forth in the definitive agreement, instruments and documents to be entered into or executed by NHC and the investor. Moreover, under no circumstances shall the number of common shares to be issued under this financing transaction exceed 24% of the issued and outstanding of common shares or such other percentages that will result in the regulators requiring the Company to seek shareholders' approval for this financing transaction. The issuance of the Debentures and the Warrants was unanimously approved by the board of directors of NHC. NHC Communications Inc. is a leading provider of products and services enabling the management of voice and data communications for telecommunication service providers. NHC's ControlPoint(R) solutions utilize a high-performance software driven Element Management System (EMS) controlling an automated, true any-to-any copper cross-connect switch, to enable incumbent local exchange carriers (ILECs) and other service providers to remotely perform the four key tasks that historically have required manual on-site management. These four tasks fundamental to all operations are loop qualification, deployment and provisioning, fallback switching and service migration of Voice and Data services including DSL and T1/ E1. Using ControlPoint(R) NHC's customers avoid the risk of human error and dramatically reduce labour and operating costs. NHC maintains offices in Montreal, Quebec, and Paris, France. "ControlPoint(R)" is a registered trademark of NHC Communications Inc. NHC may be contacted through its web site at www.nhc.com .